(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
In paper an influence of waste dump “Chrobrów” on groundwater and tributary of the Bóbr river was described. This waste dump was installed in former gravel excavation. For first 10 years it had no leak stopper and sewage water could freely infiltrate. Geological structure of the waste dump subsoil is unfavourable because garbage are directly stored on gravels with high filtration coefficient which make migration of pollutants easy. At the moment the waste dump has a leak stopper made from bentonite composite but there are still polluted groundsunderneath. In this paper was analyzed data about ground- and surface water quality from years 1994 – 2004. It was found that the quality of groundwater deteriorated, especially in years 1999 and 2002. The most worsening was noted in case of chlorides, ammonia nitrogen, sodium and potassium. Unfortunately there is no data before 1994 so there is no information about hydrogeochemical background. Increased values of all groundwater components infirst period of investigation are results of exploitation in years 1984 – 1994, when waste dump had no leak stopper.But later deterioration of groundwater quality can not be explained in this way. It should be drawn a conclusion that the seal of waste dump bottom does not work correctly. It was found that there is no negative impact of waste dump on surface water what is caused by absence of hydraulic contact between river and groundwater on investigated area.